Morphological responses to nitrogen stress deficiency of a new heterotrophic isolated strain of Ebro Delta microbial mats. - Villagrasa, Eduard; Ferrer-Miralles, Neus; Millach, Laia; Obiol, Aleix; Creus, Jordi; Esteve, Isabel; Solé, Antonio (Protoplasma, 2019)
Microorganisms living in hypersaline microbial mats frequently form consortia under stressful and changing environmental conditions. In this paper, the heterotrophic strain DE2010 from a microalgae consortium (Scenedesmus sp. DE2009) from Ebro Delta microbial mats has been phenotypically and genotypically characterized and identified. In addition, changes in the morphology and biomass of this bacterium in response to nitrogen deficiency stress have been evaluated by correlative light and electron microscopy (CLEM) combining differential interference contrast (DIC) microscopy and transmission electron microscopy (TEM) and scanning electron microscopy (SEM). These isolated bacteria are chemoorganoheterotrophic, gram-negative, and strictly aerobic bacteria that use a variety of amino acids, organic acids, and carbohydrates as carbon and energy sources, and they grow optimally at 27 °C in a pH range of 5 to 9 and tolerate salinity from 0 to 70‰ NaCl. The DNA-sequencing analysis of the 16S rRNA and nudC and fixH genes and the metabolic characterization highlight that strain DE2010 corresponds to the species Ochrobactrum anthropi. Cells are rod shaped, 1-3 μm in length, and 0.5 μm wide, but under deprived nitrogen conditions, cells are less abundant and become more round, reducing their length and area and, consequently, their biomass. An increase in the number of pleomorphic cells is observed in cultures grown without nitrogen using different optical and electron microscopy techniques. In addition, the amplification of the fixH gene confirms that Ochrobactrum anthropi DE2010 has the capacity to fix nitrogen, overcoming N2-limiting conditions through a nifH-independent mechanism that is still unidentified.